PENERAPAN MEDIA POP-UP BOOK UNTUK PEMAHAMAN SUB TEMA KETAMPAKAN RUPA BUMI DI SEKOLAH DASAR - Safrina Junita; Munzir (Program Studi Pendidikan Guru Sekolah Dasar, 2020)
This research is motivated by the results of observations and interviews conducted by researchers in several elementary schools in Aceh Besar and Banda Aceh which explain that teachers are still having trouble finding suitable media for learning, especially on themes that contain a lot of reading, one of them is in grade III elementary school , as in the sub-theme of the appearance of the earth with the characteristics of the sub-theme in the form of abstract material concepts and understanding is obtained by reading a lot so that an innovation is needed so that students remain active and can increase students' understanding during learning. The purpose of this research is to apply pop-up book learning media for students' understanding of the sub-theme of the appearance of the earth. The results of the application of the pop-up book media on the sub-theme of appearance of the earth can improve the understanding of students in class III SD 69 of the sub-theme. This is evidenced by the acquisition of student learning outcomes in the posttest with a percentage of 86.2% of students included in the category